2001
DOI: 10.1074/jbc.c000652200
|View full text |Cite
|
Sign up to set email alerts
|

The Mycobacterium tuberculosis cmaA2 Gene Encodes a Mycolic Acid trans-Cyclopropane Synthetase

Abstract: Infection with Mycobacterium tuberculosis remains a major global health emergency. Although detailed understanding of the molecular events of M. tuberculosis pathogenesis is still limited, recent genetic analyses have implicated specific lipids of the cell envelope as important effectors in M. tuberculosis pathogenesis. We have shown that pcaA, a novel member of a family of M. tuberculosis S-adenosyl methionine (SAM)-dependent methyl transferases, is required for ␣-mycolic acid cyclopropanation and lethal chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 18 publications
(30 reference statements)
7
114
1
4
Order By: Relevance
“…Another mycolic acid synthase, PcaA, was shown to be important for dormancy since pcaA knock-out strains lost their ability to persist, although not replicated in a mouse model (Glickman et al, 2000). Studies in M. tuberculosis have shown that Rv0503c (CmaA2), found in this study to be fourfold upregulated during anaerobisis, is required for the synthesis of the trans-cyclopropane rings of keto-and methoxymycolates (Glickman et al, 2001). Cyclopropanation of mycolic acids is a modification that is associated with pathogenic bacteria and is not common in the cell wall of saprophytic species such as M. smegmatis (Minnikin et al, 1982).…”
Section: Cell Wallmentioning
confidence: 91%
“…Another mycolic acid synthase, PcaA, was shown to be important for dormancy since pcaA knock-out strains lost their ability to persist, although not replicated in a mouse model (Glickman et al, 2000). Studies in M. tuberculosis have shown that Rv0503c (CmaA2), found in this study to be fourfold upregulated during anaerobisis, is required for the synthesis of the trans-cyclopropane rings of keto-and methoxymycolates (Glickman et al, 2001). Cyclopropanation of mycolic acids is a modification that is associated with pathogenic bacteria and is not common in the cell wall of saprophytic species such as M. smegmatis (Minnikin et al, 1982).…”
Section: Cell Wallmentioning
confidence: 91%
“…Ligase Gene Disruptions in M. tuberculosis-Gene disruption was performed by specialized transduction of lig::hyg R cassettes using temperature-sensitive mycobacteriophages as described previously (19,20). The lig⌬::hyg R gene disruption cassettes were constructed by PCR amplifying genomic DNA segments flanking each ligase gene and inserting them on either side of the hygromycin resistance gene in plasmid pJSC407, a cloning vector containing the hyg R marker, a cos site, and a unique PacI restriction site for packaging into phAE87.…”
Section: Methodsmentioning
confidence: 99%
“…DNA Ligation Assay-A 36-bp DNA duplex containing a centrally placed 3Ј-OH/5Ј-PO 4 nick was formed by annealing two 18-mer oligodeoxyribonucleotides to a complementary 36-mer strand as described previously (18,19). The 18-mer constituting the 5Ј phosphate-terminated strand d(ATTCCGATAGTGACTACA) was 5Ј 32 P-labeled and gelpurified, then annealed to the complementary 36-mer DNA (the template strand) in the presence of a 3Ј-OH 18-mer strand d(CATAT-CCGTGTCGCCCTT).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of these are PcaA and MmaA2 mutants that express mycolic acids without α-mycolate cyclopropanation [10,11], CmaA2 mutants that are unable to effect trans-cyclopropanation in the oxygenated mycolates [12], or MmaA4 and MmaA3 mutants that produce mycolic acids without distal functionality of the oxygenated mycolates [13,14]. The significance of secreted free mycolic acids as potential role players in the manifestation of tuberculosis was recently noted when Ojha et al (2008) [15] demonstrated their role in biofilm formation during in vitro growth of M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%